Description of the ancestral processes for the recognition by the Arhuaco people of the biofortified beans Agrosavia Rojo 43 - López López, Antonio José; Izquierdo Cujar, Yeimy Alejandra; Tofiño Rivera, Adriana Patricia; Rozo Leguizamón, Yanine; Rochel Ortega, Elizabeth; Gómez Latorre, Douglas Andrés (2024)
The economy of the Arhuaco people, one of the four ancestral communities settled in the Sierra Nevada de Santa Marta, revolves around communal agricultural and livestock production. This is why their primary and secondary education processes prioritize subjects that promote work in the gardens, among which beans, as a traditional and ceremonial food, are prominent. In the context of this growing community, food production requires the development of new teaching tools to disseminate agricultural techniques and practices derived from the intercultural technological innovation processes of agrosavia. Through this educational booklet, the aim is to integrate the worldview of ancestral communities into the management of technical knowledge, in such a way that it guarantees the conservation of their identity and their notion of life territory. The technological hybridization contained in this document—resulting from harmonizing traditional and agroecological thoughts— is presented to the Arhuaco communities and the global scientific community as a fundamental tool for caring for the environment. It also serves to teach the “bonachi” or younger brother to recognize that humans belong to Mother Earth and not the other way around, a call that spiritual leaders make as guardians of the heart of the world.